The main protease 3CLpro of the SARS-CoV-2 virus: how to turn an enemy into a helper - Svetlana V. Belenkaya; Svetlana V. Belenkaya; Svetlana V. Belenkaya; Iuliia A. Merkuleva; Olga I. Yarovaya; Olga I. Yarovaya; Varvara Yu. Chirkova; Elena A. Sharlaeva; Daniil V. Shanshin; Ekaterina A. Volosnikova; Sergey Z. Vatsadze; Mikhail V. Khvostov; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Despite the long history of use and the knowledge of the genetics and biochemistry of E. coli, problems are still possible in obtaining a soluble form of recombinant proteins in this system. Although, soluble protein can be obtained both in the cytoplasm and in the periplasm of the bacterial cell. The latter is a priority strategy for obtaining soluble proteins. The fusion protein technology followed by detachment of the fusion protein with proteases is used to transfer the target protein into the periplasmic space of E. coli. We have continued for the first time to use the main viral protease 3CL of the SARS-CoV-2 virus for this purpose. We obtained a recombinant 3CL protease and studied its complex catalytic properties. The authenticity of the resulting recombinant enzyme, were confirmed by specific activity analysis and activity suppression by the known low-molecular-weight inhibitors. The catalytic efficiency of 3CL (0.17 ± 0.02 µM-1-s-1) was shown to be one order of magnitude higher than that of the widely used tobacco etch virus protease (0.013 ± 0.003 µM-1-s-1). The application of the 3CL gene in genetically engineered constructs provided efficient specific proteolysis of fusion proteins, which we demonstrated using the receptor-binding domain of SARS-CoV-2 spike protein and GST fusion protein. The solubility and immunochemical properties of RBD were preserved. It is very important that in work we have shown that 3CL protease works effectively directly in E. coli cells when co-expressed with the target fusion protein, as well as when expressed as part of a chimeric protein containing the target protein, fusion partner, and 3CL itself. The results obtained in the work allow expanding the repertoire of specific proteases for researchers and biotechnologists.